Laparospic Resection of Gastrointestinal Stromal Tumors (GIST) of Small Intestine: A case report - Navarini, Daniel; Albuquerque, Antônio Benincá; Rovani, André Luca Boeira; Reffatti, Diego; Reichert, Paulo Roberto; Madalosso, Carlos Augusto Scussel (Clinical and Biomedical Research, 2019)
Although gastrointestinal stromal tumors (GISTs) are a rare type of cancer, they are the commonest mesenchymal tumors of the gastrointestinal tract (GIT). GISTs can affect any segment of the GIT, but the usual location is the stomach, followed by the small intestine. Surgical resection of the tumor is the gold standard treatment for localized GISTs, and in patients with inoperable and metastatic disease, imatinib mesylate is the standard treatment. Pathological diagnosis is based on morphology and immunohistochemical findings. We report the case of a 55-year-old man with jejunal GIST presenting with endophytic and exophytic growth, located in the proximal jejunum. He had history of melena, anemia and one episode of enterorrhagia, and was treated with surgical resection of the lesion. Keywords: Gastrointestinal stromal tumor; gastrointestinal neoplasms